Short communication: The activity of brigatinib in patients with disease progression after next generation anaplastic lymphoma tyrosine kinase inhibitors and an exploratory analysis of circulating tumor DNA. (March 2022) - Stinchcombe, Thomas E.; Wang, Xiaofei; Doebele, Robert C.; Drusbosky, Leylah M.; Gerber, David E.; Horn, Leora; Bertino, Erin M.; Liu, Geoff; Villaruz, Liza C.; Ross Camidge, D.
Highlights: Brigatinib demonstrated activity after second-generation ALK TKI's. The ORR was similar after 1 st or 2 nd line therapy with second generation ALK TKI's. ctDNA testing for ALK resistance mutations is feasible when ctDNA is detectable. Abstract: Background: Brigatinib, a second generation anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitor (TKI), is central nervous system (CNS) penetrant and active against anaplastic lymphoma kinase ( ALK ) resistance mutations. We prospectively studied the activity of brigatinib in patients with disease progression after second generation ALK TKIs. Methods: Patients with stage IIIB/IV ALK + non-small cell lung cancer (NSCLC), and progressive disease after second ALK TKIs were eligible. Cohort A enrolled patients with disease progression on any second ALK TKI, cohort B enrolled patients with disease progression after first-line therapy with alectinib, and cohort C enrolled patients who experienced disease progression on standard dose brigatinib. Brigatinib treatment was 90 mg daily for seven days and then escalated to 180 mg daily in cohorts A and B, and 240 mg daily in cohort C. The primary endpoint was objective response rate (ORR), and a 2-stage design was used. The intended enrollment was 20 patients in stage 1, and 20 patients in stage 2. Results: The study was closed due to slow accrual. Between March 2017 and June 2020, 32 patients received study therapy; three patients in cohort A moved to cohort C after initial progression for a total of 35 study subjects. Of the 32 patients, 16 (50%) were male, the median age was 55 years (range 32–76), and patients received a median number of 2 prior ALK TKI's (range 1–3). Cohort A enrolled 27 patients, cohort B enrolled four patients, and cohort C enrolled four patients. The ORR in cohorts A, B, and C was 33% (95% confidence interval (CI: 16% to 54%), 25% (95% CI: 0.63% to 81%), and 0%, respectively. Conclusion: Brigatinib has activity in ALK positive NSCLC patients with disease progression after second generation ALK TKIs.